Waterproof wear-resistant SPC floor and preparation method thereof
By compounding EPDM rubber, boron nitride, montmorillonite, and activated calcium carbonate, the problems of brittleness and weak interfacial bonding of SPC flooring were solved, resulting in improved wear resistance and hardness, excellent mechanical properties, and good dimensional stability.
Patent Information
- Application Number
- CN202511123752.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-12
- Publication Date
- 2025-12-02
AI Technical Summary
Existing SPC flooring has a high PVC resin content and low calcium powder content, resulting in significant material brittleness. It is prone to breakage at low temperatures, has weak interfacial bonding, and affects its impact resistance and dimensional stability.
The product is made by compounding EPDM rubber with boron nitride and montmorillonite, combined with activated calcium carbonate. This improves the interfacial bonding between PVC resin and calcium powder, thereby enhancing the hardness and toughness of the flooring. Nano-silica particles are used to improve dispersibility and dimensional stability.
It significantly improves the abrasion resistance and hardness of SPC flooring, enhances mechanical properties, reduces dimensional change rate, and extends service life.
Smart Images

Figure CN121045700A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of SPC flooring technology, and in particular to a waterproof and wear-resistant SPC floor and its preparation method. Background Technology
[0002] Traditional wood flooring, relying on natural wood resources, faces severe challenges to its sustainable development. SPC (stone-plastic composite) flooring, as a new type of environmentally friendly material, achieves excellent properties such as waterproofing, moisture resistance, and insect resistance through its composite structure of polyvinyl chloride resin and highly filled calcium powder, and it does not contain heavy metals or harmful substances such as formaldehyde.
[0003] However, the existing SPC flooring still has the following technical defects: (1) Due to the high proportion of PVC resin and low amount of calcium powder filling, the existing SPC flooring is brittle and prone to breakage in low temperature environment; at the same time, the interfacial bonding force between PVC resin and calcium powder is weak, which can easily cause stress concentration and further reduce the impact resistance of the material. (2) In order to improve toughness, although EPDM rubber can be used as a toughening agent, its excellent weather resistance and elasticity can effectively alleviate the brittleness of PVC, but on the one hand, the flexible characteristics of EPDM lead to insufficient surface hardness of composite board, which is easy to produce indentation; on the other hand, the compatibility between rubber phase and resin matrix is insufficient, and filler is easy to fall off during wear; on the other hand, the high elasticity of EPDM is easy to cause board expansion and contraction under temperature difference, which affects the stability of the installation.
[0004] While directly increasing the amount of calcium powder filling can improve hardness, it will further deteriorate toughness, leading to an increased risk of brittle cracking of the board. Traditional surface modification technology has limited effect on strengthening the filler-resin interface and is difficult to balance mechanical properties and dimensional stability. Summary of the Invention
[0005] The purpose of this invention is to address the shortcomings of existing technologies by proposing a waterproof and wear-resistant SPC floor and its preparation method.
[0006] A waterproof and wear-resistant SPC flooring, the raw materials of which include, by weight: 5-15 parts EPDM rubber, 40-60 parts polyvinyl chloride resin, 10-20 parts activated calcium carbonate, 1-5 parts boron nitride, 1-5 parts montmorillonite, 1-3 parts dopamine hydrochloride, 1-4 parts plasticizer, 1-2 parts stabilizer, and 1-2 parts dispersant.
[0007] Preferably, the plasticizer is at least one selected from dibutyl phthalate, tributyl citrate, trioctyl citrate, and acetylated tributyl citrate.
[0008] Preferably, the stabilizer is a calcium-zinc stabilizer.
[0009] Preferably, the dispersant is a polyacrylate dispersant.
[0010] Preferably, activated calcium carbonate is prepared by the following steps: calcium carbonate is added to sodium hydroxide solution, stirred at 40-50℃ for 5-10 min, centrifuged, washed, and vacuum dried; the product and tetraethyl orthosilicate are added to an ethanol aqueous solution and stirred evenly, the pH of the system is adjusted to 7.5-8.5, ultrasonically treated for 1-3 h at an ultrasonic temperature of 40-60℃, centrifuged, washed, and vacuum dried.
[0011] More preferably, the particle size of calcium carbonate is 5-15 μm.
[0012] More preferably, the mass ratio of calcium carbonate to tetraethyl orthosilicate is 5-15:1-5.
[0013] More preferably, the ultrasonic frequency is 30-50kHz.
[0014] The preparation method of the above-mentioned waterproof and wear-resistant SPC flooring includes the following steps: S1. Add boron nitride and montmorillonite to sulfuric acid aqueous solution and stir for 10-30 min at a stirring temperature of 60-70℃. Cool to room temperature, centrifuge, wash, vacuum dry, add to Tris buffer, add dopamine hydrochloride and stir for 20-30 h, centrifuge, wash, vacuum dry to obtain composite filler. S2. Stir EPDM rubber, PVC resin, and composite filler for 5-15 minutes, then add activated calcium carbonate, plasticizer, stabilizer, and dispersant and continue stirring for 10-20 minutes to obtain the preform. S3. Plasticize the preform into sheets for 5-12 minutes at a plasticizing temperature of 140-160℃; then compress the sheets at 130-140℃ and 4-6MPa for 20-30 minutes, cool to 60-70℃, and then cold press at 7-9MPa for 1-5 minutes.
[0015] Preferably, in S1, the concentration of the sulfuric acid aqueous solution is 6-8 mol / L, and the pH value of the Tris buffer solution is 7.5-8.5. Beneficial effects
[0016] This invention introduces ethylene propylene diene monomer (EPDM) rubber, which absorbs impact energy through its elastic segments, effectively mitigating the brittle fracture tendency of PVC resin. However, traditional EPDM modification leads to decreased hardness and interfacial debonding. This invention addresses this by combining boron nitride and montmorillonite, which form a layered structure that bears a certain load in the resin matrix, dispersing stress and making the internal structure of the flooring denser, thus increasing hardness. Furthermore, after activation, the boron nitride and montmorillonite compound forms polydopamine on the structural surface, which not only has strong interfacial bonding with PVC resin and EPDM rubber, preventing the separation of fillers from the resin matrix, delaying crack propagation, and significantly improving wear resistance, but also creates a denser network, greatly enhancing hardness.
[0017] This invention activates calcium carbonate to induce the formation of a microporous structure on its surface, and then combines it with nano-silica particles. The resulting activated calcium carbonate not only reduces filler agglomeration and improves dispersibility, but also enhances the bonding force with polyvinyl chloride resin and EPDM rubber. Furthermore, it maintains excellent dimensional deformation rate even with large addition amounts, while exhibiting high tensile strength and excellent mechanical properties.
[0018] This invention helps to improve the unfavorable interfacial interaction between PVC resin and calcium powder. Moreover, the large amount of calcium powder filling in SPC boards increases the overall hardness and mechanical strength of the boards. At the same time, the product has a small dimensional change rate, good dimensional stability, and improves the service life of the flooring. Attached Figure Description
[0019] Figure 1 The graph shows a comparison of the coefficient of friction, heating warpage, and cold and hot warpage of the SPC flooring obtained in Example 5 and Comparative Examples 1-2.
[0020] Figure 2 This is a comparison chart of the hardness and heating dimensional change rate of the SPC flooring obtained in Example 5 and Comparative Examples 1-2.
[0021] Figure 3 The graph shows a comparison of the static bending strength and tensile strength of the SPC flooring obtained in Example 5 and Comparative Examples 1-2. Detailed Implementation
[0022] The present invention will be further explained below with reference to specific embodiments.
[0023] The polyvinyl chloride resin used below is sourced from Manner Plastics, LP, USA, and its grade is PVC X4165. The ethylene propylene diene monomer (EPDM) rubber used below is sourced from Jilin Petrochemical and its grade is 2027M. The calcium-zinc stabilizer used below is purchased from Shandong Mouxin New Material Technology Co., Ltd. The polyacrylate dispersant used below is BASF Efka EFKA-4550. Example 1
[0024] A waterproof and wear-resistant SPC flooring, the raw materials of which include: 50g of EPDM rubber, 400g of polyvinyl chloride resin, 100g of activated calcium carbonate, 10g of boron nitride, 10g of montmorillonite, 10g of dopamine hydrochloride, 10g of dibutyl phthalate, 10g of calcium-zinc stabilizer, and 10g of polyacrylate dispersant.
[0025] Activated calcium carbonate is prepared by the following steps: 50g of calcium carbonate with a particle size of 5-15μm is added to 300g of 0.1mol / L sodium hydroxide solution, stirred at 40℃ for 5min, centrifuged, washed, and vacuum dried; the product is added to 50g of 45% ethanol aqueous solution with 10g of tetraethyl orthosilicate and stirred evenly, the pH of the system is adjusted to 7.5 with ammonia, and ultrasonically treated for 1h at 40℃ and 30kHz, centrifuged, washed, and vacuum dried.
[0026] The preparation method of the above-mentioned waterproof and wear-resistant SPC flooring includes the following steps: S1. Add boron nitride and montmorillonite to 300g of 6mol / L sulfuric acid aqueous solution, stir at 500r / min for 10min at 60℃, cool to room temperature, centrifuge, wash, vacuum dry, add to 200g of pH=7.5 Tris buffer, add dopamine hydrochloride, stir at 100r / min for 20h, centrifuge, wash, vacuum dry to obtain composite filler; S2. Add EPDM rubber, PVC resin, and composite filler to a high-speed mixer and stir at 300 r / min for 5 min. Add activated calcium carbonate, dibutyl phthalate, calcium-zinc stabilizer, and polyacrylate dispersant and continue stirring for 10 min to obtain the preform. S3. Feed the preformed material into a two-roll plasticizer and plasticize it into sheets. The plasticizing temperature is 140℃ and the plasticizing time is 5 minutes. Then, add it into a pressure molding machine and press it into sheets at a temperature of 130℃ and a pressure of 4MPa. Hold the pressure for 20 minutes, cool it to 60℃, and then cold press it at a pressure of 7MPa for 1 minute. Then, print the pattern and cut it into samples. Example 2
[0027] A waterproof and wear-resistant SPC flooring, the raw materials of which include: 150g of EPDM rubber, 600g of polyvinyl chloride resin, 200g of activated calcium carbonate, 50g of boron nitride, 50g of montmorillonite, 30g of dopamine hydrochloride, 40g of tributyl citrate, 20g of calcium-zinc stabilizer, and 20g of polyacrylate dispersant.
[0028] Activated calcium carbonate is prepared by the following steps: 150g of calcium carbonate with a particle size of 5-15μm is added to 600g of 0.4mol / L sodium hydroxide solution, stirred at 50℃ for 10min, centrifuged, washed, and vacuum dried; the product and 50g of tetraethyl orthosilicate are added to 150g of 55% ethanol aqueous solution and stirred evenly, the pH of the system is adjusted to 8.5 with ammonia water, ultrasonically treated for 3h at 60℃ and 50kHz, centrifuged, washed, and vacuum dried.
[0029] The preparation method of the above-mentioned waterproof and wear-resistant SPC flooring includes the following steps: S1. Add boron nitride and montmorillonite to 500g of 8mol / L sulfuric acid aqueous solution, stir at 700r / min for 30min at 70℃, cool to room temperature, centrifuge, wash, vacuum dry, add to 300g of pH=8 Tris buffer solution, add dopamine hydrochloride, stir at 200r / min for 30h, centrifuge, wash, vacuum dry to obtain composite filler; S2. Add EPDM rubber, PVC resin and composite filler to a high-speed mixer and stir at 500 r / min for 15 min. Add activated calcium carbonate, tributyl citrate, calcium zinc stabilizer and polyacrylate dispersant and continue stirring for 20 min to obtain the preform. S3. The preformed material is fed into a two-roll plasticizer and plasticized into sheets at a temperature of 160°C for 12 minutes. It is then added to a pressure molding machine and pressed at a temperature of 140°C and a pressure of 6MPa for 30 minutes. After cooling to 70°C, it is cold-pressed at a pressure of 9MPa for 5 minutes. Then, the pattern is printed and the sample is cut. Example 3
[0030] A waterproof and wear-resistant SPC flooring, the raw materials of which include: 120g of EPDM rubber, 450g of polyvinyl chloride resin, 120g of activated calcium carbonate, 40g of boron nitride, 20g of montmorillonite, 25g of dopamine hydrochloride, 20g of trioctyl citrate, 18g of calcium-zinc stabilizer, and 12g of polyacrylate dispersant.
[0031] Activated calcium carbonate is prepared by the following steps: 120g of calcium carbonate with a particle size of 5-15μm is added to 400g of 0.3mol / L sodium hydroxide solution, stirred at 42℃ for 9min, centrifuged, washed, and vacuum dried; the product and 20g of tetraethyl orthosilicate are added to 120g of 50% ethanol aqueous solution and stirred evenly, the pH of the system is adjusted to 8 with ammonia water, and ultrasonically treated for 2.5h at 45℃ and 45kHz, centrifuged, washed, and vacuum dried.
[0032] The preparation method of the above-mentioned waterproof and wear-resistant SPC flooring includes the following steps: S1. Add boron nitride and montmorillonite to 350g of 7.5mol / L sulfuric acid aqueous solution, stir at 550r / min for 25min at 62℃, cool to room temperature, centrifuge, wash, vacuum dry, add to 280g of Tris buffer solution with pH=8.5, add dopamine hydrochloride, stir at 120r / min for 28h, centrifuge, wash, vacuum dry to obtain composite filler; S2. Add EPDM rubber, PVC resin, and composite filler to a high-speed mixer and stir at 350 r / min for 12 min. Add activated calcium carbonate, trioctyl citrate, calcium-zinc stabilizer, and polyacrylate dispersant and continue stirring for 12 min to obtain the preform. S3. The preformed material is fed into a two-roll plasticizer and plasticized into sheets at a temperature of 155℃ for 6 minutes. It is then added to a compression molding machine and pressed at a temperature of 137℃ and a pressure of 4.5MPa for 28 minutes. After cooling to 64℃, it is cold-pressed at a pressure of 8.5MPa for 2 minutes. Then, the pattern is printed and the sample is cut. Example 4
[0033] A waterproof and wear-resistant SPC flooring, the raw materials of which include: 80g of EPDM rubber, 550g of polyvinyl chloride resin, 180g of activated calcium carbonate, 20g of boron nitride, 40g of montmorillonite, 15g of dopamine hydrochloride, 30g of trioctyl citrate, 12g of calcium-zinc stabilizer, and 18g of polyacrylate dispersant.
[0034] Activated calcium carbonate is prepared by the following steps: 80g of calcium carbonate with a particle size of 5-15μm is added to 500g of 0.2mol / L sodium hydroxide solution, stirred at 48℃ for 7min, centrifuged, washed, and vacuum dried; the product and 40g of tetraethyl orthosilicate are added to 80g of 50% ethanol aqueous solution and stirred evenly, the pH of the system is adjusted to 8 with ammonia water, and ultrasonic treatment is carried out for 1.5h at 55℃ and 35kHz, centrifuged, washed, and vacuum dried.
[0035] The preparation method of the above-mentioned waterproof and wear-resistant SPC flooring includes the following steps: S1. Add boron nitride and montmorillonite to 450g of 6.5mol / L sulfuric acid aqueous solution, stir at 650r / min for 15min at 68℃, cool to room temperature, centrifuge, wash, vacuum dry, add to 220g of Tris buffer solution with pH=8.5, add dopamine hydrochloride, stir at 180r / min for 22h, centrifuge, wash, vacuum dry to obtain composite filler; S2. Add EPDM rubber, PVC resin and composite filler to a high-speed mixer and stir at 450 r / min for 8 min. Add activated calcium carbonate, trioctyl citrate, calcium zinc stabilizer and polyacrylate dispersant and continue stirring for 18 min to obtain the preform. S3. The preformed material is fed into a two-roll plasticizer and plasticized into sheets at a temperature of 145℃ for 10 minutes. It is then added to a compression molding machine and pressed at a temperature of 133℃ and a pressure of 5.5MPa for 22 minutes. After cooling to 66℃, it is cold-pressed at a pressure of 7.5MPa for 4 minutes. Then, the pattern is printed and the sample is cut. Example 5
[0036] A waterproof and wear-resistant SPC flooring, the raw materials of which include: 100g of EPDM rubber, 500g of polyvinyl chloride resin, 150g of activated calcium carbonate, 30g of boron nitride, 30g of montmorillonite, 20g of dopamine hydrochloride, 25g of tributyl acetyl citrate, 15g of calcium-zinc stabilizer, and 15g of polyacrylate dispersant.
[0037] Activated calcium carbonate is prepared by the following steps: 100g of calcium carbonate with a particle size of 5-15μm is added to 450g of 0.25mol / L sodium hydroxide solution, stirred at 45℃ for 8min, centrifuged, washed, and vacuum dried; the product is added to 100g of 50% ethanol aqueous solution with 30g of tetraethyl orthosilicate and stirred evenly, the pH of the system is adjusted to 8 with ammonia, and ultrasonically treated for 2h at 50℃ and 40kHz, centrifuged, washed, and vacuum dried.
[0038] The preparation method of the above-mentioned waterproof and wear-resistant SPC flooring includes the following steps: S1. Add boron nitride and montmorillonite to 400g of 7mol / L sulfuric acid aqueous solution, stir at 600r / min for 20min at 65℃, cool to room temperature, centrifuge, wash, vacuum dry, add to 250g of Tris buffer solution with pH=8.5, add dopamine hydrochloride, stir at 150r / min for 25h, centrifuge, wash, vacuum dry to obtain composite filler; S2. Add EPDM rubber, PVC resin and composite filler to a high-speed mixer and stir at 400 r / min for 10 min. Add activated calcium carbonate, tributyl acetyl citrate, calcium zinc stabilizer and polyacrylate dispersant and continue stirring for 15 min to obtain the preform. S3. Feed the preformed material into a two-roll plasticizer and plasticize it into sheets. The plasticizing temperature is 150℃ and the plasticizing time is 8 minutes. Then, add it into a pressure molding machine and press it into sheets at a temperature of 135℃ and a pressure of 5MPa. Hold the pressure for 25 minutes, cool it to 65℃, and then cold press it at a pressure of 8MPa for 3 minutes. Finally, print the pattern and cut the sample.
[0039] Comparative Example 1 A waterproof and wear-resistant SPC flooring, the raw materials of which include: 100g of EPDM rubber, 500g of polyvinyl chloride resin, 150g of activated calcium carbonate, 40g of boron nitride, 40g of montmorillonite, 25g of tributyl acetylacetic acid, 15g of calcium-zinc stabilizer, and 15g of polyacrylate dispersant.
[0040] Activated calcium carbonate is prepared by the following steps: 100g of calcium carbonate with a particle size of 5-15μm is added to 450g of 0.25mol / L sodium hydroxide solution, stirred at 45℃ for 8min, centrifuged, washed, and vacuum dried; the product is added to 100g of 50% ethanol aqueous solution with 30g of tetraethyl orthosilicate and stirred evenly, the pH of the system is adjusted to 8 with ammonia, and ultrasonically treated for 2h at 50℃ and 40kHz, centrifuged, washed, and vacuum dried.
[0041] The preparation method of the above-mentioned waterproof and wear-resistant SPC flooring includes the following steps: S1. Add boron nitride and montmorillonite to 400g of 7mol / L sulfuric acid aqueous solution, stir at 600r / min for 20min, stirring temperature is 65℃, cool to room temperature, centrifuge, wash, and vacuum dry to obtain composite filler; S2. Add EPDM rubber, PVC resin and composite filler to a high-speed mixer and stir at 400 r / min for 10 min. Add activated calcium carbonate, tributyl acetyl citrate, calcium zinc stabilizer and polyacrylate dispersant and continue stirring for 15 min to obtain the preform. S3. Feed the preformed material into a two-roll plasticizer and plasticize it into sheets. The plasticizing temperature is 150℃ and the plasticizing time is 8 minutes. Then, add it into a pressure molding machine and press it into sheets at a temperature of 135℃ and a pressure of 5MPa. Hold the pressure for 25 minutes, cool it to 65℃, and then cold press it at a pressure of 8MPa for 3 minutes. Finally, print the pattern and cut the sample.
[0042] Comparative Example 2 A waterproof and wear-resistant SPC flooring, the raw materials of which include: 100g of EPDM rubber, 500g of polyvinyl chloride resin, 150g of activated calcium carbonate, 30g of boron nitride, 30g of montmorillonite, 20g of dopamine hydrochloride, 25g of tributyl acetyl citrate, 15g of calcium-zinc stabilizer, and 15g of polyacrylate dispersant.
[0043] Activated calcium carbonate is prepared by mixing 100g of calcium carbonate with a particle size of 5-15μm with 8.65g of nano-silica.
[0044] The preparation method of the above-mentioned waterproof and wear-resistant SPC flooring includes the following steps: S1. Add boron nitride and montmorillonite to 400g of 7mol / L sulfuric acid aqueous solution, stir at 600r / min for 20min at 65℃, cool to room temperature, centrifuge, wash, vacuum dry, add to 250g of Tris buffer solution with pH=8.5, add dopamine hydrochloride, stir at 150r / min for 25h, centrifuge, wash, vacuum dry to obtain composite filler; S2. Add EPDM rubber, PVC resin and composite filler to a high-speed mixer and stir at 400 r / min for 10 min. Add activated calcium carbonate, tributyl acetyl citrate, calcium zinc stabilizer and polyacrylate dispersant and continue stirring for 15 min to obtain the preform. S3. Feed the preformed material into a two-roll plasticizer and plasticize it into sheets. The plasticizing temperature is 150℃ and the plasticizing time is 8 minutes. Then, add it into a pressure molding machine and press it into sheets at a temperature of 135℃ and a pressure of 5MPa. Hold the pressure for 25 minutes, cool it to 65℃, and then cold press it at a pressure of 8MPa for 3 minutes. Finally, print the pattern and cut the sample.
[0045] The coefficient of friction of the SPC flooring obtained in Example 5 and Comparative Examples 1-2 was determined according to GB / T 3960-2016 "Plastics - Test Method for Sliding Friction and Wear". An abrasion testing machine was used, with a test load of 200 N and an abrasion time of 2 hours. The heating warpage and cold / heat warpage of the SPC flooring obtained in Example 5 and Comparative Examples 1-2 were determined according to GB / T 34440-2017 "Rigid Polyvinyl Chloride Flooring".
[0046] like Figure 1 As shown, the SPC flooring obtained in Example 5 had the lowest coefficient of friction, heating warpage, and cold and hot warpage, which was better than the other groups (P < 0.05).
[0047] The hardness of the SPC flooring obtained in Example 5 and Comparative Examples 1-2 was determined according to GB / T 2411-2008 "Plastics and Hard Rubber – Determination of Indentation Hardness (Shore Hardness) Using a Hardness Tester". The dimensional change rate under heat of the SPC flooring obtained in Example 5 and Comparative Examples 1-2 was determined according to GB / T 34440-2017 "Rigid Polyvinyl Chloride Flooring".
[0048] like Figure 2 As shown, the SPC flooring obtained in Example 5 had the highest hardness and the smallest heating dimensional change rate, which was better than the other groups (P < 0.05).
[0049] The static bending strength of the SPC flooring obtained in Example 5 and Comparative Examples 1-2 was determined in accordance with GB / T 17657-2022 "Test Methods for Physical and Chemical Properties of Wood-based Panels and Decorative Wood-based Panels".
[0050] The SPC flooring obtained in Example 5 and Comparative Examples 1-2 was cut into 30mm × 30mm × 4mm specimens. The tensile strength of each group of specimens was determined according to GB / T1040.1-2018 "Determination of tensile properties of plastics - Part 1: General".
[0051] like Figure 3 As shown, the SPC flooring obtained in Example 5 had the highest static bending strength and tensile strength, which were superior to the other groups (P < 0.05).
[0052] The volatile gases (formaldehyde and benzene) of the SPC flooring obtained in Example 5 and Comparative Examples 1-2 were tested according to GB / T 18883-2022 "Indoor Air Quality Standard". No volatile gases (formaldehyde and benzene) were detected in the SPC flooring obtained in Example 5 and Comparative Examples 1-2.
[0053] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A waterproof and wear-resistant SPC flooring, characterized in that, Its raw materials, by weight, include: 5-15 parts of EPDM rubber, 40-60 parts of polyvinyl chloride resin, 10-20 parts of activated calcium carbonate, 1-5 parts of boron nitride, 1-5 parts of montmorillonite, 1-3 parts of dopamine hydrochloride, 1-4 parts of plasticizer, 1-2 parts of stabilizer, and 1-2 parts of dispersant.
2. The waterproof and wear-resistant SPC flooring according to claim 1, characterized in that, The plasticizer is at least one of dibutyl phthalate, tributyl citrate, trioctyl citrate, and acetylated tributyl citrate.
3. The waterproof and wear-resistant SPC flooring according to claim 1, characterized in that, The stabilizer is a calcium-zinc stabilizer.
4. The waterproof and wear-resistant SPC flooring according to claim 1, characterized in that, The dispersant is a polyacrylate dispersant.
5. The waterproof and wear-resistant SPC flooring according to claim 1, characterized in that, Activated calcium carbonate is prepared by the following steps: calcium carbonate is added to sodium hydroxide solution, stirred at 40-50℃ for 5-10 min, centrifuged, washed, and vacuum dried; the product and tetraethyl orthosilicate are added to an ethanol aqueous solution and stirred evenly, the pH of the system is adjusted to 7.5-8.5, ultrasonically treated for 1-3 h at an ultrasonic temperature of 40-60℃, centrifuged, washed, and vacuum dried.
6. The waterproof and wear-resistant SPC flooring according to claim 5, characterized in that, The particle size of calcium carbonate is 5-15 μm.
7. The waterproof and wear-resistant SPC flooring according to claim 5, characterized in that, The mass ratio of calcium carbonate to tetraethyl orthosilicate is 5-15:1-5.
8. The waterproof and wear-resistant SPC flooring according to claim 5, characterized in that, The ultrasonic frequency is 30-50kHz.
9. A method for preparing the waterproof and wear-resistant SPC flooring as described in any one of claims 1-8, characterized in that, Includes the following steps: S1. Add boron nitride and montmorillonite to sulfuric acid aqueous solution and stir for 10-30 min at a stirring temperature of 60-70℃. Cool to room temperature, centrifuge, wash, vacuum dry, add to Tris buffer, add dopamine hydrochloride and stir for 20-30 h, centrifuge, wash, vacuum dry to obtain composite filler. S2. Stir EPDM rubber, PVC resin, and composite filler for 5-15 minutes, then add activated calcium carbonate, plasticizer, stabilizer, and dispersant and continue stirring for 10-20 minutes to obtain the preform. S3. Plasticize the preform into sheets for 5-12 minutes at a plasticizing temperature of 140-160℃; then compress the sheets at 130-140℃ and 4-6MPa for 20-30 minutes, cool to 60-70℃, and then cold press at 7-9MPa for 1-5 minutes.
10. The method for preparing the waterproof and wear-resistant SPC flooring according to claim 9, characterized in that, In S1, the concentration of the sulfuric acid aqueous solution is 6-8 mol / L, and the pH value of the Tris buffer is 7.5-8.5.